A COMPREHENSIVE SURVEY ON REAL TIME INDUCTION MOTOR FAILURE DIAGNOSIS AND ANALYSIS (ASEAN Engineering Journal, 2025)
The efficient and reliable operation of induction motors is of paramount importance in industrial processes, commercial applications, and residential settings. The timely detection and diagnosis of failures in these motors are crucial for preventing costly downtime and optimizing maintenance strategies. This review article presents a comprehensive survey of real-time induction motor failure diagnosis and analysis techniques. The article begins by outlining the significance of induction motors in various sectors and the economic implications of motor failures. It then delves into the various types of faults that can affect induction motors, including electrical, mechanical, and thermal anomalies. A detailed exploration of the state-of-the-art diagnostic methods follows, encompassing both traditional and modern approaches. The survey covers a wide range of diagnostic techniques, including vibration analysis, current and voltage signature analysis, thermal imaging, acoustic monitoring, and artificial intelligence-based methods. The strengths and limitations of each approach are discussed, along with their applicability to different types of faults. Moreover, the integration of multiple techniques into hybrid systems is explored as a means to enhance diagnostic accuracy. Real-time monitoring and data acquisition play a pivotal role in the proposed diagnostic strategies. The article provides insights into sensor technologies, data acquisition protocols, and the utilization of Machine Learning.